2019
DOI: 10.1016/j.ijdevneu.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional network connectivity changes in children with attention‐deficit hyperactivity disorder: A resting‐state fMRI study

Abstract: The study aimed to investigate the pathologic mechanism of functional brain regions in attention‐deficit hyperactivity disorder (ADHD) patients through making comparisons of normal and ADHD children from the perspective of the network nodes of brain network and the intensity of functional connection between bilateral of hemispheres by resting‐state functional magnetic resonance imaging (fMRI). Thirty‐five ADHD and forty‐two children were examined by resting‐state functional magnetic resonance imaging (fMRI) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
2
23
0
1
Order By: Relevance
“…Here, injury in network nodes was interpreted as a reduction in the influence of local network communication on other parts of the network, suggesting a breakdown in the nodes' functional interactions in a network, which can be a sign of decompensation or imbalance. DC was increased in the right inferior frontal gyrus, the right cingulate gyrus, the left superior temporal gyrus, the left medial temporal gyrus, the lingual gyrus of the right occipital lobe, the right posterior cerebellar lobe, and the left side of the pons and midbrain, which meant increased importance of these regions in the brain of patients with DEACMP [16]. One explanation for the higher degree centrality values could be that the hyperactivation in these Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, injury in network nodes was interpreted as a reduction in the influence of local network communication on other parts of the network, suggesting a breakdown in the nodes' functional interactions in a network, which can be a sign of decompensation or imbalance. DC was increased in the right inferior frontal gyrus, the right cingulate gyrus, the left superior temporal gyrus, the left medial temporal gyrus, the lingual gyrus of the right occipital lobe, the right posterior cerebellar lobe, and the left side of the pons and midbrain, which meant increased importance of these regions in the brain of patients with DEACMP [16]. One explanation for the higher degree centrality values could be that the hyperactivation in these Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Degree centrality, a directly quantifiable index to measure the importance of brain network nodes and reflects the functional network "hub" properties, is the most reliable centrality metric in large-scale networks [14][15][16]. Conceptualizing the brain as a network is potentially helpful for researchers to investigate the integrated neuronal network abnormalities in the early stages of some neuropsychiatric disorders [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increased ReHo in right dorsal anterior cingulate cortex and left lingual gyrus, and the decreased ReHo in right cerebellum were associated with higher ADHD symptom scores in the ADHD group ( An et al, 2013 ). Meantime, decreased DC was observed in the head of the right pallidum, caudate and putamen and in the left postcentral cortex ( Di Martino et al, 2013 ), as well as right posterior cingulate gyrus and frontoparietal network ( Jiang et al, 2019 ). Also, it was found that children with ADHD exhibited increased DC in the cerebellar anterior lobe, cingulate gyrus and middle occipital cortex, and increased VMHC in bilateral superior frontal, middle occipital, and cerebellar anterior lobes ( Jiang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meantime, decreased DC was observed in the head of the right pallidum, caudate and putamen and in the left postcentral cortex ( Di Martino et al, 2013 ), as well as right posterior cingulate gyrus and frontoparietal network ( Jiang et al, 2019 ). Also, it was found that children with ADHD exhibited increased DC in the cerebellar anterior lobe, cingulate gyrus and middle occipital cortex, and increased VMHC in bilateral superior frontal, middle occipital, and cerebellar anterior lobes ( Jiang et al, 2019 ). The findings above have proven that the R-fMRI indices can successfully capture the dysfunctions in the brains of ADHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Stronger as well as weaker connectivity was also described in studies with other patients, such as i.e. preterm‐born children at school‐age (Finke et al., 2015; Wehrle et al., 2018), children with ADHD (Jiang et al., 2019), or adults after traumatic brain injury (Hillary et al, 2011).…”
Section: Discussionmentioning
confidence: 66%